Factors Predicting Quality of Life among Early Surgical Menopausal Women - Chanphong, Janya; Techatraisak, Kitirat; Sa-nga-areekul, Nutchaya (Nursing Science Journal of Thailand, 2024)
Purpose: To study the predicting factors on quality of life among early surgical menopausal women including education, occupation, income, perceive general self-efficacy, self-care, and social support. Design: Predictive correlational study design. Methods: The participants consisted of 113 early surgical menopausal women who came to follow-up after surgery at the obstetric-gynecological clinic at a university hospital in Bangkok during March 2022 until May 2023. Data were collected using a demographic questionnaire, General Self-Efficacy Questionnaire, Menopausal Self-Care Questionnaire, Multidimensional Scale of Perceived Social Support and the Menopause-Specific Quality of Life Questionnaire. Descriptive statistics and multiple linear regression were applied to the data analysis. Main findings: The results revealed that all factors could explain 39.2 % of the variance in quality of life (R2 = .154). The factors that significantly predicted quality of life among early surgical menopausal women were surgical menopausal symptoms ( = .275, p < .003) and perceived social support ( = - .256, p < .024). Conclusion and recommendations: Healthcare team should promote family, friends and significant persons to support the women in early surgical menopausal period and try to promote them how to reduce surgical menopausal symptoms for increasing their quality of life.